Affidavit Sebagai Alat Bukti Terhadap Perjanjian Jual-Beli Dibawah Tangan Apabila Salah Satu Pihaknya Meninggal Dunia - Angreni, Ni Kadek Ditha; Bagiastra, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020), 2020)
Proof of the sale and purchase of land rights without being accompanied by the deed of the Land Deed Author of which one of the parties dies, then in this condition the heir does not recognize the underhand agreement or because he knows that one of the parties who binds himself has died, then the other does not fulfilling his achievements. This research will try to examine issues regarding the proof of sale and purchase of land rights that are not proven by the Official Certifier Of Title Deeds if one party dies This research was carried out through a normative legal study method with using statute approach and conceptual approach. After going through discussion and analysis, finally, it can be concluded that Land purchase agreements made under legal hands under Article 1320 Indonesian Civil Code and fulfill the conditions of the sale and purchase agreements under customary law, but do not necessarily transfer the rights to their land. Proof of agreement on the sale and purchase of land rights made under the hand if one of his parties dies can be done with affidavit.